KIPRAH POLITIK PAGUYUBAN PASUNDAN PERIODE 1927-1959 - Andre Bagus Irshanto (Diakronika, 2017)
“KIPRAH POLITIK PAGUYUBAN PASUNDAN PERIODE 1927-1959”. The author takes the topic of Paguyuban Pasundan with the above title, because it is based on the results of the study of literature by the author, that there is still the lack of works that discuss Paguyuban Pasundan, especially about political activities. The main issues that will be raised in this thesis is that Paguyuban Pasundan is not limited active in social and cultural sectors but also actively engaged in politics. Based on the main issue can be developed into three formulation of research: What is the background to the Paguyuban Pasundan? How is the political role of the Paguyuban Pasundan period 1927-1959? How is the end of political struggle Paguyuban Pasundan in 1959? The method used is the historical method which consists of four stages, namely Heuristic, Criticism, Interpretation, Historiography, and to be helped by using an interdisciplinary approach from the social sciences (especially of Sociology and Politics). The technique that author uses is the study of literature related to the theme of the author analyzed. Based on the results of the study of literature by the author, Paguyuban Pasundan period 1927-1959 has an important role, especially in the political field. In the period 1927-1942 establishing PPPKI, GAPI and active in the Volksraad. The period of 1942- 1945 some of its members active in the formation of Japanese agencies suchas newspapers Tjahaja, PETA and Java Hokokai. Period 1945-1950 actively opposed the establishment of Negara Pasundan founded by the Dutch and the last period of 1950-1959 which Paguyuban Pasundan involvement in the 1955 general election.